Mycobacterium tuberculosis RpfE promotes simultaneous Th1‐ and Th17‐type T‐cell immunity via TLR4‐dependent maturation of dendritic cells. Issue 7 (12th May 2015) - Choi, Han‐Gyu; Kim, Woo Sik; Back, Yong Woo; Kim, Hongmin; Kwon, Kee Woong; Kim, Jong‐Seok; Shin, Sung Jae; Kim, Hwa‐Jung
<x xml:space="preserve">Abstract</x> Reciprocal induction of the Th1 and Th17 immune responses is essential for optimal protection against Mycobacterium tuberculosis (Mtb); however, only a few Mtb antigens are known to fulfill this task. A functional role for resuscitation‐promoting factor (Rpf) E, a latency‐associated member of the Rpf family, in promoting naïve CD4+ T‐cell differentiation toward both Th1 and Th17 cell fates through interaction with dendritic cells (DCs) was identified in this study. RpfE induces DC maturation by increasing expression of surface molecules and the production of IL‐6, IL‐1β, IL‐23p19, IL‐12p70, and TNF‐α but not IL‐10. This induction is mediated through TLR4 binding and subsequent activation of ERK, p38 MAPKs, and NF‐κB signaling. RpfE‐treated DCs effectively caused naïve CD4+ T cells to secrete IFN‐γ, IL‐2, and IL‐17A, which resulted in reciprocal expansions of the Th1 and Th17 cell response along with activation of T‐bet and RORγt but not GATA‐3. Furthermore, lung and spleen cells from Mtb‐infected WT mice but not from TLR4−/− mice exhibited Th1 and Th17 polarization upon RpfE stimulation. Taken together, our data suggest that RpfE has the potential to be an effective Mtb vaccine because of its ability to activate DCs that simultaneously induce both Th1‐ and Th17‐polarized T‐cell expansion.